Stroke Recurrence Rate and Risk Factors Among Stroke Survivors in Sub-Saharan Africa: A Systematic Review - Mbalinda, Scovia Nalugo; Kaddumukasa, Mark; Najjuma, Josephine Nambi; Kaddumukasa, Martin; Nakibuuka, Jane; Burant, Christopher J; Moore, Shirley; Blixen, Carol; Katabira, Elly T; Sajatovic, Martha (Neuropsychiatric Disease and Treatment, 2024)
Purpose: Evidence supporting secondary stroke in sub-Saharan Africa is scarce. This study describes the incidence of stroke recurrence and associated risk factors in sub-Saharan Africa. Methods and Materials: Scientific databases were systematically searched from January 2000 to December 2022 for population- based observational studies, case-control or cohort studies of recurrent stroke involving adults aged 18 years and above in sub-Saharan Africa (SSA). We assessed the quality of the eligible studies using the Critical Appraisal Skills Program (CASP) checklist for observational studies. Results: Six studies met the inclusion criteria and were included in this study. Stroke recurrence rates in SSA ranged from 9.4% to 25%. Majority of the studies were conducted from Western Africa and showed that stroke recurrence rates are high within sub-Saharan Africa ranging from 2% to 25%. The known stroke risk factors such as hypertension, chronic alcohol consumption, etc., remained the leading causes of stroke recurrence. The studies reported a higher mortality rate ranging from 20.5 −23% among those with recurrent strokes compared to primary strokes. Conclusion: This systematic review is an update and summary of the available literature on stroke recurrence within sub-Saharan Africa. Further studies are warranted to assess the outcomes and burden of stroke recurrence in SSA.
Keywords: Stroke recurrence; Sub-Saharan Africa; Risk factors; Secondary prevention; Cardiovascular disease